Internet marketing and direct marketing to increase room occupancy at Ayodya Resort Bali - Ni Komang Nova Ari Susanti; I Gusti Agung Mas Krisna Komala Sari; Tyas Raharjeng Pamularsih (Politeknik Negeri Bali, 2020)
Purpose: This study examines the influence of internet marketing and direct marketing on room occupancy at Ayodya resort Bali in the period 2017 to 2019. It also finds out which variable has the most dominant influence. Research methods: This research used a mixed methodology of qualitative and quantitative. The data source used are primary data collected from observations and interview and secondary data in the form of room night and occupancy. The data obtained will be processed using multiple linear regression analysis techniques to determine the improvements offered by internet marketing and direct marketing to increase room occupancy at Ayodya Resort Bali. Results and discussion: The results show that variable internet marketing has positive and significant influences partially with significance value 0.000 and direct marketing with significance value 0.000 to the room occupancy at Ayodya resort Bali. The effective contributions obtained indicate that internet marketing provides a very good contribution reached 56 percent than direct marketing only gives a small effect only reached 33.83 percent. The total effect of independent variables reaching 90.3 percent on room occupancy that’s mean both of them have a positive and strong partial relationship with a partial correlation analysis. Conclusion: In order to increase the effect of direct marketing, the hotel needs to improve cooperation with offline travel agents from various types of existing markets therefore Ayodya Resort Bali remains a priority.